Evaluation of vitamin C and vitamin E for prevention of postoperative adhesion: A rat uterine horn model study. Issue 3 (20th October 2014) - Atilgan, Remzi; Kuloglu, Tuncay; Ozkan, Zehra Sema; Kavak, Salih Burcin; Kumbak, Banu; Deveci, Derya; Simsek, Mehmet; Baspinar, Melike; Sapmaz, Ekrem
Abstract Aim To investigate the effectiveness of intraperitoneal vitamin C (VC) and vitamin E (VE) in the prevention of postoperative adhesion formation in a rat uterine horn model. Methods Twenty‐eight Wistar albino rats were divided into four groups in which: control group, the abdomen was opened and closed without any intervention; adhesion group, a 2‐cm linear incision was performed on the uterine horn and closed; VC group, VC was administrated i.p., and 15 min later a 2‐cm incision was performed on the uterine horn and closed; and VE group, VE was administrated i.p., and 15 min later a 2‐cm incision was performed on the uterine horn and closed. Re‐laparotomy was performed 15 days later. Right uterine horn adhesions were evaluated according to macromorphological characteristics and tissue sections were further examined for fibrosis, angiogenesis and vascular endothelial growth factor (VEGF), type I collagen and malondialdehyde (MDA) scoring. Kruskal–Wallis anova and Mann–Whitney U‐test were utilized for statistical analysis. Results Adhesion area and also strength were significantly lower in the VC group and the VE group compared with the adhesion group. Fibrosis and angiogenesis scores were observed to be significantly higher in the adhesion group compared with the VC group and the VE group. MDA and VEGF immunoreactivity were also found to be significantly lower in the VC group and the VE group compared with the adhesion group. However, there was no significant difference between the VC group and the VE group with respect to all the above parameters. Conclusion Administration of VC or VE i.p. was observed to be effective in the prevention of postoperative adhesion formation in an experimental model.